Oil Price Fluctuation, Oil Revenue and Well-being in Nigeria - Manasseh, Charles O.; Abada, Felicia C.; Ogbuabor, Jonathan E.; Okoro, Okoro E.U.; Egele, Aja Ebeke; Ozuzu, Kenneth C. (International Journal of Energy Economics and Policy, 2018)
Using annual time series data which covers the period 1981 to 2014 and multiple regression techniques, the study investigate the impact of oil price fluctuation and oil revenue on well-being in Nigeria. The findings suggest that oil price fluctuations have no significant impact on well-being, while oil revenue is observed to have a significant and positive impact on well-being. Notwithstanding the insignificant impact of oil price fluctuation, further investigation using Johanson cointegration test shows the existence of long run relationship in the series. This implies that, as oil prices increases/decreases, so does well-being of the people. In like manner, we also found that, as the oil revenue increases/decreases, so does the well-being of the people. In view of the findings, we suggest that government should save more at the time oil boom – that is when oil price rises above its benchmark. Furthermore, we are of the opinion that the control and management of the excess crude account (ECA) should be solely delegated to Central Bank of Nigeria with no form of interference. Keywords: Oil price fluctuation, Oil Revenue, Well-being, Nigeria JEL Classifications: E39, I31 DOI: https://doi.org/10.32479/ijeep.5943